2014
DOI: 10.2147/clep.s39981
|View full text |Cite
|
Sign up to set email alerts
|

Systemic AA amyloidosis: epidemiology, diagnosis, and management

Abstract: The term “amyloidosis” encompasses the heterogeneous group of diseases caused by the extracellular deposition of autologous fibrillar proteins. The global incidence of amyloidosis is estimated at five to nine cases per million patient-years. While amyloid light-chain (AL) amyloidosis is more frequent in developed countries, amyloid A (AA) amyloidosis is more common in some European regions and in developing countries. The spectrum of AA amyloidosis has changed in recent decades owing to: an increase in the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
146
1
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(160 citation statements)
references
References 54 publications
0
146
1
13
Order By: Relevance
“…4 Similarly, Real de Asúa et al reported a mean age of 66 years among 24 AL amyloidosis patients admitted to a hospital in Spain between 2000 and 2010. 23 In another study with 232 AL amyloidosis patients with cardiac dysfunction, median age at presentation was 59 years. 24 In this study, we observed an increase in AL amyloidosis prevalence over a 9-year period (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015), coupled with stable incidence.…”
Section: Discussionmentioning
confidence: 99%
“…4 Similarly, Real de Asúa et al reported a mean age of 66 years among 24 AL amyloidosis patients admitted to a hospital in Spain between 2000 and 2010. 23 In another study with 232 AL amyloidosis patients with cardiac dysfunction, median age at presentation was 59 years. 24 In this study, we observed an increase in AL amyloidosis prevalence over a 9-year period (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015), coupled with stable incidence.…”
Section: Discussionmentioning
confidence: 99%
“…SAP binds to all types of amyloid precursors in a calcium-dependent manner, stabilizing their tertiary structure. [14] SAP is a physiological component of the glomerular basal membrane in kidneys, the basal membranes in skin, liver, lungs, blood vessels; it is a component of microfibrils lining the elastic membranes. These microfibrils structurally resemble amyloid fibrils.…”
Section: Resultsmentioning
confidence: 99%
“…24 hours urine protein may guide in diagnosis and the need for renal biopsy when diagnostic ambivalence arises due to equivocal vasculitic profile laboratory tests. [11] Conclusion:-Undifferentiated connective tissue disease may lead to renal involvement in the form of renal amyloidosis. Early diagnosis helps in reducing mortality.…”
Section: Discussion:-mentioning
confidence: 99%